Lipid layers on polyelectrolyte multilayers: Understanding lipid-polyelectrolyte interactions and applications on the surface engineering of nanomaterials - Diamanti, Eleftheria; Gregurec, Danijela; Romero, Gabriela; Cuellar, J. L.; Donath, E.; Moya, S. E. (Journal of Nanoscience and Nanotechnology, 2016)
In this manuscript we review work of our group on the assembly of lipid layers on top of polyelectrolyte multilayers (PEMs). The assembly of lipid layers with zwitterionic and charged lipids on PEMs is studied as a function of lipid and polyelectrolyte composition by the Quartz Crystal Microbalance. Polyelectrolyte lipid interactions are studied by means of Atomic Force Spectroscopy. We also show the coating of lipid layers for engineering different nanomaterials, i.e., carbon nanotubes and poly(lactic-co-glycolic) nanoparticles and how these can be used to decrease in vitro toxicity and to direct the intracellular localization of nanomaterials.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Atomic Force Spectroscopy; Cell Uptake; Lipid Bilayers; Polyelectrolyte Multilayer Films; Quartz Crystal Microbalance